Is there interspecific fruit set in distylous, synchronopatric species of Erythroxylum P. Browne (Erythroxylaceae)? - L. L. Barreto; L. D. A. Araujo; T. F. F. de Sá; L. P. Felix; M. F. Fay; C. C. Castro (Brazilian Journal of Biology)
Abstract Sympatric congeneric species that overlap the flowering period and have morphologically similar flowers tend to be pollinated by the same groups of pollinators, facilitating interspecific pollination and hybridization. If that situation involves distylous taxa, interspecific fruit set will theoretically rely on the match of sexual organs of the different species, because distylous plants only set fruits after crosses between floral morphs that are reciprocal herkogamous (RH) and are produced in different individuals. In a Caatinga forest in NE Brazil, there are three distylous species of Erythroxylum P. Br (E. citrifolium A.St.-Hil., E. pauferrense Plowman and E. simonis Plowman; Erythroxylaceae) that overlap their flowering period and have a high similarity in floral attributes. Erythroxylum pauferrense is a rare and endemic species of the region. This study aimed to describe the distylous pattern of those three Erythroxylum species (i.e., reciprocal hercogamy, proportion of morphs in the population and breeding system) and to evaluate the reproductive isolation between them. Flowering synchrony, interspecific RH and pollination were the pre-zygotic barriers investigated, and the post-zygotic one was the fruit set after interspecific pollination experiments. The species completely overlapped their flowering periods and were pollinated by the same group of species (Apis mellifera, Tetragona sp., and Trigona spinipes). In a general matter, a low level of both intra and interspecific RH was revealed. Interspecific pollination set fruits only between E. pauferrense and E. simonis. A low level of both intra and interspecific RH was revealed for all species, except for the low-level organs of E. citrifolium. The atypical distyly observed in E. pauferrense and E simonis indicates a collapse in the distylous system and may be related to a relaxation in the interspecific incompatibility mechanism.